Trust, Happiness, and Pro-social Behavior - Carattini, Stefano; Roesti, Matthias (The Review of Economics and Statistics, 2025)
This paper combines several large-scale surveys and empirical strategies to shed new light on the determinants of cooperative behavior. We provide evidence indicating that the level of trust maximizing subjective well-being tends to be above the income maximizing level. Higher trust is also linked to more cooperative and pro-social behaviors, including the private provision of global public goods such as climate change mitigation. Consistent with “warm glow” theories of pro-social behavior, our results indicate that individuals may enjoy being more cooperative than what would lead them to maximize income, which can be reflected in higher levels of subjective well-being.